PENERAPAN MANAJEMEN OPERASIONAL YANG DITERAPKAN PT RUBYCON INDONESIA - Fendy Cuandra; Conny Agustin; Elinda Nurul H.D.B.S; Febby Huang; Jacky Jacky; Metta Noviani (Bajang Institute, 2023)
Operational management is one of the most important parts of solving problems in manufacturing companies because they always have to deal with ever-changing environmental conditions. One of the efforts to win the competition in the field of operations is to design and produce goods or services effectively and efficiently in accordance with the tastes of customers. Therefore, the company must plan and control the storage of raw materials properly, so that the production process in the company can run smoothly, so that the optimal quantity is achieved, and the cost savings in the company can be used for production. Rubycon Indonesia was founded in 1992 as a joint venture between Rubycon Corporation from Japan and PT Trinitron Indonesia. The company initially operated as an electrolyte processing manufacturer and expanded into a tanta, film, and ceramics manufacturer. Currently, the company also manufactures several additional products such as power supply modules, EMI (Electromagnetic) filters and bluetooth modules. As a company engaged in the electronics industry, PT Rubycon Indonesia also realizes the importance of maintaining information security and protecting client data. In order to develop and strengthen its business, PT Rubycon Indonesia also continues to conduct research and development to produce new and innovative products. Overall, PT Rubycon Indonesia is a company committed to producing high quality products and conducting business in a socially and environmentally responsible manner.